2020
DOI: 10.2337/db19-1128
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin-1 Mitigates Cognitive Dysfunction in Prediabetic Rats With No Alteration in Insulin Sensitivity

Abstract: Previous studies showed that 12 weeks of high-fat diet (HFD) consumption caused not only prediabetes but also cognitive decline and brain pathologies. Recently, necrostatin-1 (nec-1), a necroptosis inhibitor, showed beneficial effects in brain against stroke. However, the comparative effects of nec-1 and metformin on cognition and brain pathologies in prediabetes have not been investigated. We hypothesized that nec-1 and metformin equally attenuated cognitive decline and brain pathologies in prediabetic rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 44 publications
5
42
0
Order By: Relevance
“…Collectively, all findings show that the activation of NTR1 has beneficial effects on controlling metabolic disturbance in the prediabetic model. In the current study, even though the levels of fasting blood glucose and insulin in our HFD-fed control groups seem high, they are within the pre-diabetic ranges as consistent with previous studies (Chunchai et al 2018, Jinawong et al 2020, Konda et al 2020.…”
Section: Journal Of Endocrinologysupporting
confidence: 93%
See 1 more Smart Citation
“…Collectively, all findings show that the activation of NTR1 has beneficial effects on controlling metabolic disturbance in the prediabetic model. In the current study, even though the levels of fasting blood glucose and insulin in our HFD-fed control groups seem high, they are within the pre-diabetic ranges as consistent with previous studies (Chunchai et al 2018, Jinawong et al 2020, Konda et al 2020.…”
Section: Journal Of Endocrinologysupporting
confidence: 93%
“…Our previous study reported that although the level of triglyceride was unchanged in the blood, it was increased in the liver and adipose tissue after the rats were fed with HFD for 12 to 16 weeks (Pratchayasakul et al 2011(Pratchayasakul et al , 2014. Additionally, the level of plasma HDL-C was not altered after chronic HFD consumption in this study; it might be that the duration of HFD intake was not long enough to alter the level of HDL-C (Jinawong et al 2020). In the present study, the rats were fed with HFD for total 16 weeks; however, another study from our group has reported that the reduction in plasma HDL-C levels could be achieved after 40 weeks of HFD consumption (Saiyasit et al 2019).…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, in the rat model of prediabetes, which is characterized by cognitive decline and brain pathology, Nec-1 improved cognitive function, synaptic plasticity and brain mitochondrial function and reduced hyperphosphorylated Tau formation. Additionally, in this model, Nec-1 attenuated necroptosis (pRIP1, RIP3), oxidative stress and microglia activation [140]. Additionally, it has been shown that Nec-1 could be efficient in improving cognitive performance in aged animals, and these effects were accompanied by decreased RIP1 level, improved synaptic plasticity and alleviated pro-inflammatory cytokine (IL-1α, IL-1β and TNFα) contents [141].…”
Section: In Vivo Studies Linking Oxidative Stress and Necroptosis In Relation To Neurodegenerative Diseasesmentioning
confidence: 78%
“…Brain mitochondrial dysfunction was observed in animal models of cardiac I/R injury, prediabetes, and Alzheimer's disease. 21,62,94,95 Despite intensive studies in both clinical and animal models have been reported the alteration of brain mitochondria in HF models. [96][97][98] However, the potential role of brain mitochondrial function in HF is rather limited.…”
Section: Future Investigationmentioning
confidence: 99%
“…The brain is the vital organ, which demand the high ATP from mitochondria for maintaining brain function. Brain mitochondrial dysfunction was observed in animal models of cardiac I/R injury, prediabetes, and Alzheimer's disease 21,62,94,95 . Despite intensive studies in both clinical and animal models have been reported the alteration of brain mitochondria in HF models 96‐98 .…”
Section: Introductionmentioning
confidence: 99%